The antiquity of Australian silcrete heat treatment: Lake Mungo and the Willandra Lakes. Issue 142 (May 2020) - Schmidt, Patrick; Hiscock, Peter
Abstract: The evolution of heat treatment for stone artefact production is a subject of major interest for our understanding of early modern humans. In this study, we examine the evidence from one region in Australia to provide a new record of the antiquity of heat treatment, explore chronological shifts in the frequency of heat treatment, and discuss the implications of these findings for early population dynamics and the technical knowledge early settlers might have brought with them. Until now, Australian heat treatment has only dated back 25000 years. This study of the Willandra Lakes, including Lake Mungo, has identified the oldest systematic evidence of heat treatment yet reported in Australia, dating to ∼42000 years. We also document time-dependent directional change in the frequency of the practice. At those early times, with over 60% of all silcrete artefacts heat-treated, we hypothesize that the practice was mastered and integrated as a recurrent technical solution to the complexities of knapping silcrete. Over time, the use of heat treatment decreased progressively until less than 10% of the artefacts were heat-treated in the terminal Holocene. This trajectory has implications for understanding the antiquity of heat treatment on the Australian continent and for investigating the factors that governed its use.